(untitled) (Bangladesh Heart Journal, 2020)
Introduction: The objectives of the present study are to describe the institutional experience, technical aspects and outcome of right ventricular outflow tract (RVOT) stenting in Tetralogy of Fallot type lesions as the initial palliation in a Bangladeshi centre. Methods: This is a retrospective, single-center study of nonrandomized, consecutive 32 patients over a 12-year period. Selected patients underwent cardiac catheterization for implanting a stent into an obstructed RVOT to improve pulmonary blood flow.Statistical data analysis was performed using SPSS 20. Results: Thirty cases had stenting in RVOT and two cases were postponed. Median age was 8.1 (3-40) months, median weight was 4.8 (3.3-11.4)kg, median procedure time was 65 (26-210) minutes and fluoroscopy time was 16 (10-75) minutes.Stents were implanted through 5F Judkins coronary guide catheter and 5F or 6F delivery sheath of ADOII device. Median stent diameter was 6 (4-7) mm. Stent length varies from 12-22 mm with median 14 mm. Oxygen saturation of the patients increased from median 60 (30 - 75)% to 91 (85-98)%. In one patient stent was embolized to aorta and was fixed to descending aorta. Two cases were postponed for short infundibular length. One patient died from non cardiac cause two months after palliation. No procedure related mortality recorded. Conclusion: Right ventricular outflow tract stenting is a good option of palliation for small babies with reduced pulmonary blood flow. In our setting we did most of the palliation to offer better quality of life who could not afford surgery or who was detected late. Bangladesh Heart Journal 2020; 35(1) : 1-5